Fluorescence in situ hybridization karyotyping reveals the presence of two distinct genomes in the taxon Aegilops tauschii - Zhao, Laibin (BMC Genomics, 2018)
BACKGROUND: Aegilops tauschii is the donor of the bread wheat D genome. Based on spike morphology, the taxon has conventionally been subdivided into ssp. tauschii and ssp. strangulata. The present study was intended to address the poor match between this whole plant morphology-based subdivision and genetic relationships inferred from genotyping by fluorescence in situ hybridization karyotyping a set of 31 Ae. tauschii accessions. RESULTS: The distribution of sites hybridizing to the two probes oligo-pTa-535 and (CTT)(10) split the Ae. tauschii accessions into two clades, designated D(t) and D(s), which corresponded perfectly with a previously assembled phylogeny based on marker genotype. The D(t) cluster was populated exclusively by ssp. tauschii accessions, while the D(s) cluster harbored both ssp. strangulata and morphologically intermediate accessions. As a result, it is proposed that Ae. tauschii ssp. tauschii is restricted to carriers of the D(t) karyotype: their spikelets are regularly spaced along the rachis, at least in the central portion of their spike. Accessions classified as Ae. tauschii ssp. strangulata carry the D(s) karyotype; their spikelets are irregularly spaced. Based on this criterion, forms formerly classified as ssp. tauschii var. meyeri have been re-designated ssp. strangulata var. meyeri. CONCLUSIONS: According to the reworking of the taxon, the bread wheat D genome was most probably donated by ssp. strangulata var. meyeri. Chromosomal differentiation reveals intra-species taxon of Ae. tauschii. Ae. tauschii ssp. tauschii has more distant relationship with breed wheat than ssp. strangulata and can be used for breeding improving effectively.